1986
DOI: 10.1136/ard.45.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid in intervertebral discs: a histopathological investigation of surgical material from 100 consecutive operations on herniated discs.

Abstract: SUMMARY Material from 100 consecutive operations on herniated discs has been investigated for amyloid. Various degrees of amyloid degeneration were found in disc tissue from 41 patients. Material from patients over 50 years old showed significantly more amyloid than that from younger patients; there was no sex difference. Eighteen patients had previously been operated on for herniated discs; seven of these (39%) had pyrophosphate deposits in their disc tissue, often in close topographical relation to amyloid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The overall prevalence of CPPD deposits in lumbosacral discs of material gained at autopsy or surgery has been reported to be between 6% and 20% [5,14] and 10% and 26%, respectively [1,7,9]. Most reports assume an association between disc degeneration and CPPD deposition due to changes in collagen and proteoglycan composition and concentration [5].…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of CPPD deposits in lumbosacral discs of material gained at autopsy or surgery has been reported to be between 6% and 20% [5,14] and 10% and 26%, respectively [1,7,9]. Most reports assume an association between disc degeneration and CPPD deposition due to changes in collagen and proteoglycan composition and concentration [5].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, fairly little is known regarding localized amyloid forms in joints and ligaments, and most studies have been focused on prevalence. Particularly knee (5) and hip (4,18–21) joints as well as intervertebral discs (6,19,22) and ligamentum flavum (23,24) have been studied in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…Elec tron microscopy has revealed that the collagen fibers exist in close proximity to amyloid fibrils [8][9][10]. These findings suggest that an affinity exists between B2M and collagen.…”
Section: Introductionmentioning
confidence: 72%